Natural Resources: A Blessing or a Curse? - Elissaios Papyrakis; Reyer Gerlagh (Fondazione Eni Enrico Mattei (FEEM), 2003)
We examine empirically the effect of natural resource abundance on economic growth. We find that natural resources have a negative impact on growth when considered in isolation, but a positive impact on growth when including in the analysis other variables such as corruption, investments, openness, terms of trade, and schooling, and treating these variables as independent. However, when we take account of the effect of natural resources on the other variables and furthermore consider the indirect effect on growth, that is, when we examine possible transmission channels, we find a strong negative effect of natural resources on growth. Finally, we calculate the relative importance of each transmission channel.
Keywords: C21; O13; Q33; 330; Natural Resources; growth; transmission channels; Natürliche Ressourcen; Wirtschaftswachstum; Regressionsanalyse; Vergleich; Welt